Profil Kemampuan Literasi Numerasi Peserta Didik SMA Pada Pembelajaran Biologi Kelas XII Pada Materi Evolusi: (Profile Of Numerical Literacy Ability High School Students XII Class in Biology Learning On Evolution Materials) - Ilham Mohammad Rizki; Suhendar Suhendar; Gina Nuranti (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study aims to determine the profile of the numeracy literacy ability of class XII students of one of the senior high schools in Sukabumi Regency in learning biology on evolution materials. The type of research used is descriptive with the sampling technique being random sampling. This research was conducted on class XII students at SMAN 1 Sukaraja in the academic year 2021/2022. The instrument used is a matter of numeracy literacy ability which refers to the indicators of Dewayani in the form of 8 multiple choice questions and 4 descriptive questions. The results showed that the content indicator had a percentage of 61% in the sufficient category, the cognitive process indicator had a percentage of 31% in the very poor category, and the context indicator had a percentage of 56% in the sufficient category with an overall average of 49% with less category. Based on these data, it can be concluded that the cognitive process indicators must be improved again with a meaningful learning process in terms of the learning model, media, and assessment provided. Keywords: Literacy Numeracy, Evolution ABSTRAK Penelitian ini bertujuan untuk mengetahui profil kemampuan literasi numerasi peserta didik kelas XII di SMA Kabupaten Sukabumi pada pembelajaran Biologi. Jenis penelitian yang digunakan adalah deskriptif dengan teknik pengambilan sampel adalah random sampling. Penelitian ini dilakukan pada peserta didik kelas XII di SMAN 1 Sukaraja tahun ajaran 2021/2022. Instrumen yang digunakan yaitu soal kemampuan literasi numerasi yang merujuk pada indikator Dewayani dengan bentuk soal pilihan ganda sebanyak 8 soal dan soal uraian sebanyak 4 soal. Hasil penelitian menunjukkan bahwa pada indikator konten memiliki perssentase sebesar 61% dengan kategori cukup, pada indikator proses kognitif memiliki persentase sebesar 31% dengan kategori sangat kurang, serta pada indikator konteks memiliki persentase 56% dengan kategori cukup dengan rata-rata keseluruhan sebesar 49% dengan kategori kurang. Berdasarkan data tersebut dapat disimpulkan bahwa pada indikator proses kognitif harus ditingkatkan kembali dengan proses pembelajaran yang bermakna dari segi model pembelajaran, media maupun asesmen yang diberikan. Kata kunci: Literasi Numerasi, Evolusi